Two New Records of Endophytic Fungi Isolated from Lindera obtusiloba in Korea: Colletotrichum citricola and Valsa ceratophora - Jae-Eui Cha; Yun-Jeong Kim; Ji-Won Kim; Ahn-Heum Eom (한국균학회지)
Lindera obtusiloba Blume, a shrub prevalent in the understory vegetation of the deciduous forests in East Asia and Korea, is known for its pharmacological properties, including antioxidant, anti-allergic, and anti-inflammatory activities. Endophytic fungi were isolated from surface-sterilized twigs and leaves of L. obtusiloba collected from Samcheok-si and Jecheon-si in Korea. The fungal strains were identified based on their morphological characteristics and molecular analyses using DNA markers such as internal transcribed spacer, large subunit rDNA, β-tubulin, chitin synthase, and glyceraldehyde-3-phosphate dehydrogenase. Here, we report two new records of endophytic fungi isolated from L. obtusiloba in Korea: Colletotrichum citricola and Valsa ceratophora. These results enhance our understanding of the diversity of endophytic fungi in L. obtusiloba and contribute to enhancing our knowledge of fungal biodiversity in Korea.